2008
DOI: 10.1186/1471-2164-9-333
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of transcriptional networks driving selenite stress response in yeasts

Abstract: Background: Stress responses provide valuable models for deciphering the transcriptional networks controlling the adaptation of the cell to its environment. We analyzed the transcriptome response of yeast to toxic concentrations of selenite. We used gene network mapping tools to identify functional pathways and transcription factors involved in this response. We then used chromatin immunoprecipitation and knock-out experiments to investigate the role of some of these regulators and the regulatory connections b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
101
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(106 citation statements)
references
References 63 publications
(140 reference statements)
5
101
0
Order By: Relevance
“…In this context, decreasing the ratio between GSH and oxidized glutathione after selenite-induced oxidative stress would influence cell viability. In addition, the latter transcriptomic study suggests that selenite also influences intracellular iron homeostasis by interfering with mitochondrial iron-sulphur cluster synthesis (Salin et al, 2008). The results of the present study demonstrating the importance of GSH-dependent Grx1p and Grx2p activity for protection against non-apoptotic death emphasize the role of GSH in defence against Se toxicity.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…In this context, decreasing the ratio between GSH and oxidized glutathione after selenite-induced oxidative stress would influence cell viability. In addition, the latter transcriptomic study suggests that selenite also influences intracellular iron homeostasis by interfering with mitochondrial iron-sulphur cluster synthesis (Salin et al, 2008). The results of the present study demonstrating the importance of GSH-dependent Grx1p and Grx2p activity for protection against non-apoptotic death emphasize the role of GSH in defence against Se toxicity.…”
Section: Discussionsupporting
confidence: 48%
“…The importance of GSH-mediated protection against Se is confirmed by observations from two global analyses in S. cerevisiae: (i) the overrepresentation of mutants in GSHmediated pathways among those mutants displaying selenite hypersensitivity (Seitomer et al, 2008); and (ii) the transcriptional induction of genes involved in these same pathways upon selenite treatment (Salin et al, 2008). In this context, decreasing the ratio between GSH and oxidized glutathione after selenite-induced oxidative stress would influence cell viability.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Yap4 belongs to this family and it has previously been shown that the gene encoding this protein is responsive to several forms of stress (Nevitt et al, 2004b;Salin et al, 2008). Its expression is regulated under osmotic stress by Hog1/Msn2 via two stress-response elements (STRE), and under oxidative stress by Msn2 and Yap1 through the STRE and Yap1 binding sites, respectively (Nevitt et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%